Games of Strategy - Dixit, Avinash [et al.] (New York W.W. Norton & Company, 2015)
Games of Strategy, famous for its simple yet accurate exposition and its great examples and exercises, has been extensively revised for this Fourth Edition. The key to its broad success is that the authors assume no prior knowledge of game theory and present the material in the most accessible way possible. With new and improved features and compelling end-of-chapter exercises, this Fourth Edition of Games of Strategy continues to engage students around the world. Known for its use of real-world examples throughout, this accessible text simplifies complex theoretical ideas and shows the value of strategic thinking in a variety of situation.
Include Index
Keywords: Policy sciences -- Decision making -- Game theory